Repositioning of the women members in the union parishasd to ensure women's empowerment in Bangladesh - Islam, Md. Jahurul Islam (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.